The Role of Therapeutic Communication in Government Policy and Covid-19 Coverage in the Media - Derivanti, Azizah Des (Indonesian Journal of Digital Society is a scientific journal, 2020)
Health communication perspective which is commonly called therapeutic communication, has a principle that is contrary to the principle of the media "bad news is good news". Therapeutic communication views the Covid-19 pandemic, there are three systems, namely the personalistic system, the naturalistic system and the biomedical system. In dealing with Covid-19, the Government referred to at least two regulations, namely Law No. 4 of 1984 and PP No.40 of 1991 discuss the Prevention of Outbreaks of Infectious Diseases in this paper is the Covid-19 virus. The media reports the Covid-19 case in detail as a symbol to make it easier to describe the chronology and development of the Covid-19 virus case. On the other hand, the patient's personal data is not displayed. The research method in this paper by the author is descriptive analysis with a qualitative approach. Keywords : Therapeutic communications, media, Covid-19